ChemInform Abstract: Algiolide A, Secoiridoid Glucoside from Mongolian Medicinal Plant Gentiana Algida. Issue 23 (June 2015) - Tanaka, Naonobu; Takekata, Minami; Kurimoto, Shin‐ichiro; Kawazoe, Kazuyoshi; Murakami, Kotaro; Damdinjav, Davaadagva; Dorjbal, Enkhjargal; Kashiwada, Yoshiki
Abstract isolation and structure elucidation